(untitled) (Altre Modernità, 2021)
The present paper proposes an analysis on video games in which anthropomorphized animals (or zoomorphed humans) are used to build narrative contexts focused on small societies and micro-communities. The aim of this paper is to observe the peculiarities in the use of anthro-zoomorphism in similar contexts, from the implications in terms of identification to the potential political message of similar products. The essay, after an introduction on the use of animals in video games and a paragraph of methodology on the choice of cases, focuses on some case studies representative of broader categories, in particular distinguishing between the political/warlike perspective and the micro-community perspective, which are linked in different ways to representations of the territory.